Therapeutic Communication As A Solution To Overcome Adolescent Problems - Tutik Astuti; Listia Dwi Febriati; Zahrah Zakiyah; Ester ratnaningsih (Edujavare Publishing, 2023)
This community service aimed to enhance parents' knowledge and therapeutic communication skills regarding adolescent issues in Padukuhan Duku, Jambidan Village. Conducted on August 1, 2023, the activity involved 17 parents, focusing on adolescent problems and solutions through counseling. Findings revealed a positive shift in knowledge levels, with a significant increase in the